Seasonal changes in population of the Amphipod Gammarus aequicauda (Martynov, 1931) - PRATO, E.; BIANDOLINO, F. (Mediterranean Marine Science, 2003)
Monthly collections were made for one year (March 2001 to February 2002) in Mar Piccolo of Taranto (Ionian sea, Italy), in order to establish the seasonal fluctuations of a population of Gammarus aequicauda (Crustacea, Amphipoda). Variations in the population structure, sex ratio and fecundity were studied. The population comprised all stages of the life cycle all year round, thus showing continuous reproduction. Size differences between males and females occurred throughout the year with males being larger than females. The recruitment of juveniles into the population occurred particularly in autumn-winter. Females consistently predominated in numbers over males during winter months. Female cephalic length was positively correlated with eggs number.